2020
DOI: 10.5249/jivr.v12i3.1371
|View full text |Cite
|
Sign up to set email alerts
|

Global School-based Student Health Survey reveals correlates of suicidal behaviors in Brunei Darussalam: a nationwide cross-sectional study

Abstract: Background: This study aimed to determine the prevalence of and correlates for suicidal behaviors among school attending adolescents in Brunei. Methods: Nationally representative cross-sectional data on (n=2599) adolescents derived from the Global School-based Health Survey in Brunei Darussalam were examined. Data on suicidal behaviors, psychosocial and demographic characteristics were analyzed using multiple logistic regression taking survey design into account.Results: Twelve months prior to being surveyed, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Of these, 76 estimates for 68 countries across 17 studies were included in meta-analysis ( fig 3 , fig 4 , fig 5 , fig 6 ), nearly all from the Global School-Based Student Health Survey. Five meta-analyses were conducted, one for each of the following WHO regions: Africa (five studies, 57 58 59 60 61 11 countries), the Americas (five studies, 62 63 64 65 66 26 countries), Eastern Mediterranean (two studies, 58 67 10 countries), South-East Asia (five studies, 58 68 69 70 71 nine countries), and Western Pacific (four studies, 58 71 72 73 12 countries). A meta-analysis was not performed for Europe owing to fewer comparable measures across a small number of countries with prevalence data for this age group.…”
Section: Resultsmentioning
confidence: 99%
“…Of these, 76 estimates for 68 countries across 17 studies were included in meta-analysis ( fig 3 , fig 4 , fig 5 , fig 6 ), nearly all from the Global School-Based Student Health Survey. Five meta-analyses were conducted, one for each of the following WHO regions: Africa (five studies, 57 58 59 60 61 11 countries), the Americas (five studies, 62 63 64 65 66 26 countries), Eastern Mediterranean (two studies, 58 67 10 countries), South-East Asia (five studies, 58 68 69 70 71 nine countries), and Western Pacific (four studies, 58 71 72 73 12 countries). A meta-analysis was not performed for Europe owing to fewer comparable measures across a small number of countries with prevalence data for this age group.…”
Section: Resultsmentioning
confidence: 99%
“…Early sexual debut was also found to be associated with physical fights according to multi-country studies [39,40]. The studies in Brunei, El Salvador, Namibia, Pakistan, Kuwait, and the USA have reported that adolescents experiencing suicide planning and other psychosocial problems were more likely to be involved in frequent physical fighting [12][13][14][15][41][42][43]. Moreover, other studies identified the associations between alcohol use, early sexual debut, and suicide planning [44,45].…”
Section: Plos Onementioning
confidence: 96%